Membrane material with surface coating and polaroid
By applying a surface-coated film material on the polarizer, the problem of glare pollution easily during use of the polarizer is solved, and production costs are reduced, achieving high hardness, high wear resistance and low moisture permeability.
Patent Information
- Application Number
- CN202510059550.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-15
- Publication Date
- 2025-04-29
AI Technical Summary
Existing polarizers are prone to glare pollution during use, and the domestic market is fierce, so production costs need to be reduced to improve market competitiveness.
A surface-coated film material is used as the outer layer of the polarizer. The coating consists of epoxy compounds, hydrophobic acrylates, surfactants, photoinitiators, diluents and solvents. A surface coating with high hardness, high wear resistance and low moisture permeability is then formed through UV glue.
Without the need for additional surface protective film, the polarizer has the characteristics of anti-fouling, anti-fingerprint, high hardness, high wear and scratch resistance, and low moisture permeability, which greatly reduces production costs.
Smart Images

Figure CN119899419A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a film material with a surface coating and a polarizer, belonging to the technical field of optical films and polarizers. Background Art
[0002] Various electronic optical films such as smart TVs, mobile phones, and tablet PCs in daily life are widely used in display devices such as liquid crystals and OLEDs made of polarizing plates as basic parts. However, when such mobile devices are in use, the polarizing plates in the display devices located on the side where the human eye observes are prone to glare pollution. One of the sources of glare is the reflected light formed by the extremely bright light source in the environment shining on the polarizing plate and reflected by the polarizing plate. The light emitted by the display device itself and the reflected light formed on the display device by the light source in the environment are superimposed on each other to form glare. Long-term use of such electronic optical films with glare will not only cause visual discomfort, but also damage vision and even cause blindness. Therefore, the surfaces of various display devices on the market are bonded with anti-glare films. At present, the hardness and wear resistance of anti-glare films are not high, and a layer of surface protection film needs to be applied on its surface to prevent the surface of the polarizer from being scratched during transportation.
[0003] In addition, display devices such as LCDs and OLEDs exported overseas will be corroded by moisture during sea transportation. Applying a layer of surface protection film on the outer surface of the polarizer observed by the human eye can isolate it from moisture corrosion.
[0004] However, the cost of polarizer surface protective film is relatively high, and it is only for process protection, and the protective film will be torn off in the end use. At present, the domestic market of polarizers is highly competitive, and each company is trying to save costs and improve market competitiveness. If the surface protective film can be omitted, the polarizer can achieve high wear resistance and scratch resistance, and low moisture permeability, which can greatly improve market competitiveness. Summary of the invention
[0005] In order to overcome the drawbacks of the prior art, the present invention provides a film material with a surface coating and a polarizer. The prepared film material with a surface coating is used as the outer layer of the polarizer, has the characteristics of anti-fouling and anti-fingerprint, high hardness, high wear resistance, scratch resistance, and low moisture permeability, and does not require a surface protective film to be attached, thereby greatly reducing the production cost of the polarizer.
[0006] The technical solution adopted by the present invention to solve its technical problem is:
[0007] A film material with a surface coating comprises a base film and a surface coating coated on a non-priming surface of the base film, wherein the coating liquid of the surface coating comprises the following components in parts by weight: 10 to 30 parts of an epoxy compound, 8 to 15 parts of a hydrophobic acrylate, 0.5 to 2.0 parts of a surfactant, 1.5 to 3.0 parts of a photoinitiator, 3 to 8 parts of a diluent and 50 to 65 parts of a solvent.
[0008] The above-mentioned film material with surface coating, the epoxy compound includes methyl acrylate and / or 1,2-epoxy-4-vinylcyclohexane of alicyclic epoxy groups containing carbon-carbon double bonds, alicyclic epoxy compounds without carbon-carbon double bonds and a mixture of oxetane, and the mixture ratio of the three is 2:2:1.
[0009] In the above-mentioned film material with surface coating, the hydrophobic acrylate includes unsubstituted straight-chain or branched alkyl acrylate with 1 to 5 carbon atoms or unsubstituted aryl acrylate.
[0010] In the above-mentioned film material with surface coating, the hydrophobic acrylate includes one or more of pentaerythritol tetraacrylate, dipentaerythritol hexaacrylate, ethylene glycol diacrylate, glycerol triacrylate and methyl acrylate.
[0011] In the above-mentioned film material with surface coating, the surfactant includes fluorine-containing acrylic compounds, fluorine-containing organosilicon compounds or organosilicon compounds; and the photoinitiator includes a mixture of a photocationic initiator and a photoradical initiator.
[0012] The above-mentioned film material with surface coating, the photocationic initiator includes one or more of diazonium salt, diaryl iodonium salt, triaryl sulfonium salt, alkyl sulfonium salt, triaryl sulfonium salt, iron aromatic salt, sulfonyloxy ketone, triaryl siloxane, diphenyl [4- (phenylthio) phenyl] - hexafluoroantimonate, diphenyl - (4-phenylthio) phenyl sulfonium hexafluorophosphate, 4-isobutylphenyl -4, -methylphenyl iodonium hexafluorophosphate and isopropyl thioxanthone; the photoradical initiator includes one or more of phenyl ketone, phosphorus, triazine, acetophenone, benzophenone, thioxanthone, benzoin, oxime compound.
[0013] In the above-mentioned film material with surface coating, the diluent includes ε-caprolactone monomer or epoxy resin monomer; the solvent includes one or more of toluene, butanone, ethyl acetate, butyl acetate, methyl isobutyl ketone, and propylene glycol methyl ether acetate.
[0014] The above-mentioned film material with surface coating has a thickness of 4 to 8 μm; and the base film is a PMMA film or a PET film.
[0015] A polarizer, the above-mentioned film material with surface coating is applied to the polarizer, and the polarizer comprises, from top to bottom, the film material with surface coating, a PVA polarizer, a film material without surface coating, a pressure-sensitive adhesive, and a release film, and the film material with surface coating and the film material without surface coating are respectively bonded to the upper and lower surfaces of the PVA polarizer by UV adhesive.
[0016] The beneficial effects of the present invention are:
[0017] The present invention uses the film material with a surface coating as the outer layer of the polarizer, which is located on the outermost side of the polarizer. It has the characteristics of anti-fouling and anti-fingerprint, high hardness, high wear resistance, anti-scratch, and low moisture permeability. No additional surface protection film is required, which greatly reduces the production cost of the polarizer. The water vapor permeability of the film material with a surface coating at 40°C and 90% humidity is 20-60g / m 2 ·24h, pencil hardness 500gf pressure test speed 0.5 ~ 2mm / s to reach 3H or more, friction resistance 500gf pressure speed 50mm / s to draw a 5cm line back and forth counted as 1 time, 20 times or more without scratches, surface coating water contact angle reaches 105° or more, ensure that when in use, no need to stick to the surface protection film. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 This is a schematic diagram of the structure of the upper polarizer of the present invention;
[0019] In the figure: 1. PVA layer; 2. UV adhesive layer; 3. Base film; 4. Film material without surface coating; 5. Surface coating; 6. Pressure-sensitive adhesive layer; 7. Release film. DETAILED DESCRIPTION
[0020] See also Figure 1 The present invention adopts an upper polarizer made of a film material with a surface functional layer, which is stacked from top to bottom in order of a surface coating 5, a base film 3, a PVA layer (polarizer) 1, a film material without a surface coating 4, a pressure-sensitive adhesive layer 6, and a release film 7. The upper and lower films in contact with the PVA layer are connected together by a UV adhesive layer 2, and the thickness of the surface coating is 4 to 8 μm. The water vapor permeability of the film material with a surface coating at 40°C and 90% humidity is 20-60g / m 2 ·24h, pencil hardness 500gf pressure test speed 0.5~2mm / s reaches 3H or more, friction resistance 500gf pressure speed 50mm / s to draw a 5cm line back and forth is counted as 1 time, 20 times or more without scratches; the water contact angle of the surface coating reaches 105° or more, so that the upper polarizer does not need to be attached with a surface protection film, and can have the characteristics of anti-fouling and anti-fingerprint, high hardness, high wear resistance, anti-scratch, and low moisture permeability, which greatly reduces the production cost of polarizers.
[0021] The coating solution for the film surface coating contains the following components in parts by weight: 10 to 30 parts of epoxy compound, 8 to 15 parts of hydrophobic acrylate, 0.5 to 2.0 parts of surfactant, 1.5 to 3.0 parts of photoinitiator, 3 to 8 parts of diluent and 50 to 65 parts of solvent. Specifically:
[0022] (1) The epoxy compound is a mixture of methacrylate and / or 1,2-epoxy-4-vinylcyclohexane of an alicyclic epoxy group containing a carbon-carbon double bond, an alicyclic epoxy compound not containing a carbon-carbon double bond, and oxetane.
[0023] The alicyclic epoxy compounds without carbon-carbon double bonds include the following structural formula (I): such as Daicel CELLOXIDE2021P, Daicel EPOLEAD GT401
[0024]
[0025] Alicyclic epoxy compounds containing carbon-carbon double bonds include 1,2-epoxy-4-vinylcyclohexane (Formula II) and methacrylates of alicyclic epoxy groups containing carbon-carbon double bonds (Formula III):
[0026] 1,2-Epoxy-4-vinylcyclohexane, such as CELLOXIDE 2000
[0027]
[0028] Methacrylate containing alicyclic epoxy groups with carbon-carbon double bonds, such as CYCLOMER M100
[0029]
[0030] Oxetanes include the following structural formula (Formula IV): Dongya Synthetic OXT-221 (DOX)
[0031]
[0032] (2) Hydrophobic acrylate
[0033] The hydrophobic acrylate composition includes an acrylate compound without any hydrophilic group, wherein the hydrophilic group includes a hydroxyl group and a carboxyl group. The reliability of the polarizer can be improved by including the hydrophobic acrylate compound, especially after the polarizer is placed under high temperature and high humidity for a long time.
[0034] The hydrophobic acrylate may include unsubstituted linear or branched alkyl acrylates having 1 to 5 carbon atoms and unsubstituted aryl acrylates, pentaerythritol tetraacrylate, dipentaerythritol hexaacrylate, ethylene glycol diacrylate, glycerol triacrylate, and methyl acrylate.
[0035] (3) Surfactants
[0036] Examples of the surfactant include fluorine-containing acrylic compounds, fluorine-containing organosilicon compounds, and organosilicon compounds, such as Shin-Etsu KY-1203, SIYEZI 4007F, and BYK3700.
[0037] (4) Photoinitiator
[0038] The photoinitiator may comprise a mixture of a photocationic initiator and a photoradical initiator.
[0039] The photocationic initiator includes one or more of diazonium salts, diaryliodonium salts, triarylsulfonium salts, alkylsulfonium salts, triarylsulfonium salts, iron aromatic salts, sulfonyloxy ketones, triarylsiloxanes, diphenyl[4-(phenylthio)phenyl]-copper(III) hexafluoroantimonate, diphenyl-(4-phenylthio)phenylsulfonium hexafluorophosphate, 4-isobutylphenyl-4,-methylphenyliodonium hexafluorophosphate and isopropylthioxanthone.
[0040] The photo radical initiator may include phenyl ketone, phosphorus, triazine, acetophenone, benzophenone, thioxanthone, benzoin, oxime compounds and mixtures thereof, such as IRGACURE 184, 1-hydroxycyclohexylphenyl ketone.
[0041] (5) Diluent
[0042] Examples of the diluent include commonly used ε-caprolactone monomers and epoxy resin monomers. Examples of the epoxy resin monomers include EPOLIGHT 100E and EPOLIGHT 400E produced by Kyoeisha.
[0043] (6) Solvent
[0044] Examples of the solvent include toluene, methyl ethyl ketone, ethyl acetate, butyl acetate, methyl isobutyl ketone, and propylene glycol methyl ether acetate.
[0045] Description of the proportion of each ingredient added:
[0046] The amount of the epoxy compound is preferably 10 to 30 parts by weight, preferably methacrylate and / or 1,2-epoxy-4-vinylcyclohexane of alicyclic epoxy groups containing carbon-carbon double bonds, alicyclic epoxy compounds without carbon-carbon double bonds, and oxetane are compounded. This compounding is selected so that the epoxy compound and the hydrophobic acrylate undergo cross-linking reaction with each other to form a three-dimensional cross-linked network structure, enhance the cross-linking density of the coating, and improve the hardness and friction resistance. The alicyclic epoxy compound undergoes a ring-opening reaction under the initiation of a cationic initiator, and the methacrylate and / or 1,2-epoxy-4-vinylcyclohexane of alicyclic epoxy groups containing carbon-carbon double bonds can cross-link with alicyclic epoxy compounds without carbon-carbon double bonds, oxetane, and can also cross-link with hydrophobic acrylates. Oxetane can cross-link with alicyclic epoxy compounds and can also reduce the viscosity of the composition. The compounding ratio of the alicyclic epoxy methacrylate containing a carbon-carbon double bond, the alicyclic epoxy compound not containing a carbon-carbon double bond, and oxetane is 2:2:1, which can maintain the solubility of the mixture and the barrier property of the coating.
[0047] The weight portion of the above hydrophobic acrylate is preferably 8 to 15 parts. The hydrophobic acrylate can undergo a cross-linking reaction with the methacrylate containing an alicyclic epoxy group. When the amount of the hydrophobic acrylate added is less than 8 parts by weight, there is a tendency that the hardness and wear resistance cannot be met. This is because the hydrophobic acrylate used in the present invention has a high functionality, a large cross-linking density, and the carbon-carbon double bond is easy to form a polymer chain through free radical polymerization. At the same time, the presence of the ester group makes the polymerized material have a certain water resistance and oil resistance. These characteristics jointly determine that the hydrophobic acrylate forms a polymer with a tight structure and high strength during the polymerization process, and has high hardness and high wear resistance. On the other hand, when the addition amount is greater than 15 parts by weight, it will lead to an increase in water vapor permeability, and there is a tendency that the moisture resistance cannot be met, which is not preferred. This is because the hydrophobicity of the ether bond formed by the ring-opening reaction of the epoxy compound is greater than that of the ester bond, and the bond energy of the ether bond is higher. Ether compounds show higher stability in chemical reactions, thereby having better hydrophobicity.
[0048] The amount of the surfactant added is 0.5 to 2.0 parts by weight, more preferably 0.8 to 1.5 parts by weight. When the amount of the surfactant added is less than 0.5 parts by weight, there is a tendency that the anti-fouling and anti-fingerprint properties cannot be satisfied. On the other hand, when it is greater than 2.0 parts by weight, there is a tendency that the surface hardness and wear resistance cannot be satisfied.
[0049] The added amount of the above-mentioned photoinitiator is preferably 1.5 to 3.0 parts by weight, more preferably 1.8 to 2.5 parts by weight. When the added amount of the photoinitiator is less than 1.5 parts by weight, the polymerization molecular weight requirement cannot be met, the cross-linking density is low, the reaction speed is slow, and the efficiency is low. When the added amount is greater than 3.0 parts by weight, the initiator remains in the polymer, causing instability in the storage of the polymer.
[0050] The weight ratio of the photocationic initiator to the photoradical initiator is 1:1 to 3:1. When it is greater than 3:1, the hydrophobic acrylate will not react sufficiently, and the wear resistance and hardness will tend to decrease. When it is less than 1:1, the epoxy compound will not react sufficiently, and the water vapor transmission rate will tend to increase.
[0051] The added amount of the above diluent is preferably 3 to 8 parts by weight. When it is less than 3 parts by weight, the epoxy compound tends to be insufficiently dissolved. When it is more than 8 parts by weight, the water vapor permeability tends to increase and the abrasion resistance and hardness tend to decrease.
[0052] The amount of the solvent added is preferably 50 to 65 parts by weight. When it is less than 50 parts by weight, the coating property is reduced and the coating surface is prone to uneven coating. When it is more than 65 parts by weight, the VOC tends to increase.
[0053] The coating composition may also be added with inorganic and / or organic particles to form an anti-glare coating composition. Examples of inorganic particles include silicon dioxide, aluminum oxide, magnesium aluminum silicate, titanium dioxide, tin oxide, and zinc oxide, and examples of organic particles include acrylic resins, polystyrene resins, epoxy resins, silicone resins, styrene-acrylic acid copolymer resins, polyethylene resins, polyvinylidene fluoride resins, and polyvinyl fluoride resins.
[0054] The coating composition can also be added with an antistatic agent, and the antistatic agent is preferably used from the viewpoint of stability of optical properties, appearance, antistatic effect and antistatic effect when heated and humidified. There is no particular limitation on the type of conductive polymer, wherein, it is particularly preferred to use conductive polymers such as polyaniline and polythiophene. The antistatic agent of one or more conductive polymers can also be used in combination. In addition, a dopant can be added to the conductive polymer as required, and polystyrene sulfonic acid components can be used as a dopant, and a high-valent metal compound of a halogen element containing iodine, bromine, and chlorine components can also be used. When containing an epoxy-containing silane coupling agent and using an organic conductive polymer (for example, polythiophene) in the surface coating, as a dopant, it is preferred to use components other than the sulfonic acid component. In addition, the antistatic agent can also select ionic compounds, conductive particles, organosilicon compounds, nano-scale carbon nanotubes, etc. Among these, it can be used alone or in combination with 2 or more.
[0055] The present invention will be further described below in conjunction with the embodiments.
[0056] Example 1
[0057] Preparation of coating composition:
[0058]
[0059]
[0060] First add ε-caprolactone monomer and toluene into the preparation barrel and stir to mix evenly, then add CELLOXIDE2021P, CYCLOMER M100, OXT-221 (DOX), pentaerythritol tetraacrylate in turn and stir to mix evenly, finally add KY-1203, diphenyl-(4-phenylthio)phenylsulfonium hexafluorophosphate (CPI-100P), IRGACURE 184, and PMMA particles and stir to mix evenly.
[0061] When preparing and storing the above environment, please avoid direct sunlight, you can turn on the yellow light.
[0062] A method for preparing a PMMA film material with a surface coating, the steps are as follows:
[0063] The prepared surface coating composition was applied to the non-priming surface of the PMMA film (model HX-40UF), and after drying, UV irradiation and curing was performed to obtain a PMMA film with a surface coating, the coating thickness of which was 5 μm. The original film performance test is shown in Table 1.
[0064] A method for preparing a polarizer, comprising the following steps:
[0065] S1. Unwind the PVA original film at the first unwinding position, and perform swelling, dyeing, bridging, stretching, washing, fixing and drying to obtain a PVA polarizer; adhere a PMMA film material with a surface coating and a PMMA film material without a surface coating to the upper and lower surfaces of the PVA polarizer respectively by UV glue, the PMMA film material with a surface coating is the outer layer of the polarizer, and the PMMA film material without a surface coating is the inner layer.
[0066] S2. Unwind the release film at the second unwinding station, apply PSA glue, dry it in a drying oven, laminate it to the inner layer, and rewind it.
[0067] S3, the upper semi-finished polarizer is unwound on the cutting line, and is cut and edge-grinded to obtain a finished polarizer sheet.
[0068] The performance test of the polarizer without surface protective film is shown in Table 1.
[0069] Example 2
[0070] Preparation of coating composition:
[0071]
[0072]
[0073] First add ε-caprolactone monomer and butanone into the preparation barrel and stir to mix evenly, then add EPOLEADGT401, CYCLOMER M100, OXT-221 (DOX), dipentaerythritol hexaacrylate in turn and stir to mix evenly, finally add KY-1203, diphenyl-(4-phenylthio)phenylsulfonium hexafluorophosphate (CPI-100P), and IRGACURE 184 and stir to mix evenly.
[0074] When preparing and storing the above environment, please avoid direct sunlight, you can turn on the yellow light.
[0075] A method for preparing a PMMA film with a surface coating, the steps are as follows:
[0076] The prepared surface coating composition was applied to the non-priming surface of the PMMA film (model HX-40UF), and after drying, UV irradiation and curing was performed to obtain a PMMA film with a surface coating, the coating thickness of which was 8 μm. The original film performance test is shown in Table 1.
[0077] A method for preparing a polarizer, comprising the following steps:
[0078] S1. Unwind the PVA original film at the first unwinding position, and perform swelling, dyeing, bridging, stretching, washing, fixing and drying to obtain PVA polarizers; adhere a PMMA film material with a surface coating and a PMMA film material without a surface coating to the upper and lower surfaces of the PVA polarizers respectively by UV glue, the PMMA film material with a surface coating is an outer layer, the PMMA film material without a surface coating is an inner layer, and a PSA glue layer is adhered to the inner layer.
[0079] S2, unwind the release film at the second unwinding station, apply PSA glue, dry it in a drying oven, adhere it to the inner layer, and rewind it.
[0080] S3, the upper semi-finished polarizer is unwound on the cutting line, and is cut and edge-grinded to obtain a finished polarizer sheet.
[0081] The performance test of the polarizer without surface protective film is shown in Table 1.
[0082] Example 3
[0083] Preparation of coating composition:
[0084]
[0085] First add ε-caprolactone monomer and toluene into the preparation barrel and stir to mix evenly, then add EPOLEADGT401, CYCLOMER M100, OXT-221 (DOX), and glycerol triacrylate in turn and stir to mix evenly, and finally add KY-1203, diphenyl-(4-phenylthio)phenylsulfonium hexafluorophosphate (CPI-100P), and IRGACURE 184 and stir to mix evenly.
[0086] When preparing and storing the above environment, please avoid direct sunlight, you can turn on the yellow light.
[0087] A method for preparing a PMMA film with a surface coating, the steps are as follows:
[0088] The prepared surface coating composition was applied to the non-priming surface of the PMMA film (model HX-40UF), and after drying, UV irradiation and curing was performed to obtain a PMMA film with a surface coating, the coating thickness of which was 4 μm. The original film performance test is shown in Table 1.
[0089] A method for preparing a polarizer, comprising the following steps:
[0090] S1. Unwind the PVA original film at the first unwinding position, and perform swelling, dyeing, bridging, stretching, washing, fixing and drying to obtain PVA polarizers; adhere a PMMA film material with a surface coating and a PMMA film material without a surface coating to the upper and lower surfaces of the PVA polarizers respectively by UV glue, the PMMA film material with a surface coating is an outer layer, the PMMA film material without a surface coating is an inner layer, and a PSA glue layer is adhered to the inner layer.
[0091] S2, unwind the release film at the second unwinding station, apply PSA glue, dry it in a drying oven, adhere it to the inner layer, and rewind it.
[0092] S3, the upper semi-finished polarizer is unwound on the cutting line, and is cut and edge-grinded to obtain a finished polarizer sheet.
[0093] The performance test of the polarizer without surface protective film is shown in Table 1.
[0094] Example 4
[0095] Preparation of coating composition:
[0096]
[0097] First add EPOLIGHT 100E and toluene into the preparation barrel and stir to mix evenly, then add CELLOXIDE2021P, CYCLOMER M100, OXT-221 (DOX), pentaerythritol tetraacrylate in turn and stir to mix evenly, finally add KY-1203, diphenyl-(4-phenylthio)phenylsulfonium hexafluorophosphate (CPI-100P), and IRGACURE 184 and stir to mix evenly.
[0098] When preparing and storing the above environment, please avoid direct sunlight, you can turn on the yellow light.
[0099] A method for preparing a PMMA film with a surface coating, the steps are as follows:
[0100] The prepared surface coating composition was applied to the non-priming surface of the PMMA film (model HX-40UF), and then dried and cured by UV irradiation to obtain a PMMA film material with a coating thickness of 6 μm. The original film performance test is shown in Table 1.
[0101] A method for preparing a polarizer, comprising the following steps:
[0102] S1. Unwinding the PVA original film at the first unwinding position, swelling, dyeing, bridging, stretching, washing, fixing and drying to obtain the PVA polarizer; attaching the PMMA film material with surface coating and the PMMA film material without surface coating to the upper and lower surfaces of the PVA polarizer respectively by UV glue, the PMMA film material with surface coating is the outer layer, and the PMMA film material without surface coating is the inner layer.
[0103] S2, unwind the release film at the second unwinding station, apply PSA glue, dry it in a drying oven, adhere it to the inner layer, and rewind it.
[0104] S3, the upper semi-finished polarizer is unwound on the cutting line, and is cut and edge-grinded to obtain a finished polarizer sheet.
[0105] The performance test of the polarizer without surface protective film is shown in Table 1.
[0106] Comparative Example 1 (without addition of methacrylate containing alicyclic epoxy groups, and surfactant exceeding the limit value)
[0107] Preparation of coating composition:
[0108]
[0109] First add ε-caprolactone monomer and toluene into the preparation barrel and stir to mix evenly, then add CELLOXIDE2021P, OXT-221 (DOX), and pentaerythritol tetraacrylate in turn and stir to mix evenly, and finally add KY-1203, diphenyl-(4-phenylthio)phenylsulfonium hexafluorophosphate (CPI-100P), and IRGACURE 184 and stir to mix evenly.
[0110] When preparing and storing the above environment, please avoid direct sunlight, you can turn on the yellow light.
[0111] A method for preparing a PMMA film with a surface coating, the steps are as follows:
[0112] The prepared surface coating composition was applied to the non-priming surface of the PMMA film (model HX-40UF), and after drying, UV irradiation and curing was performed to obtain a PMMA film with a surface coating, the coating thickness of which was 5 μm. The original film performance test is shown in Table 1.
[0113] A method for preparing a polarizer, comprising the following steps:
[0114] S1. Unwinding the PVA original film at the first unwinding position, swelling, dyeing, bridging, stretching, washing, fixing and drying to obtain the PVA polarizer; attaching the PMMA film material with surface coating and the PMMA film material without surface coating to the upper and lower surfaces of the PVA polarizer respectively by UV glue, the PMMA film material with surface coating is the outer layer, and the PMMA film material without surface coating is the inner layer.
[0115] S2, unwind the release film at the second unwinding station, apply PSA glue, dry it in a drying oven, adhere it to the inner layer, and rewind it.
[0116] S3, the upper semi-finished polarizer is unwound on the cutting line, and is cut and edge-grinded to obtain a finished polarizer sheet.
[0117] The performance test of the polarizer without surface protective film is shown in Table 1.
[0118] Comparative Example 2 (without addition of hydrophobic acrylate)
[0119] Preparation of coating composition:
[0120]
[0121] First add ε-caprolactone monomer and toluene into the preparation barrel and stir to mix evenly, then add CELLOXIDE2021P, CYCLOMER M100, OXT-221 (DOX) in turn and stir to mix evenly, finally add KY-1203, diphenyl-(4-phenylthio)phenylsulfonium hexafluorophosphate (CPI-100P), and IRGACURE 184 and stir to mix evenly.
[0122] When preparing and storing the above environment, please avoid direct sunlight, you can turn on the yellow light.
[0123] A method for preparing a PMMA film with a surface coating, the steps are as follows:
[0124] The prepared surface coating composition was applied to the non-priming surface of the PMMA film (model HX-40UF), and after drying, UV irradiation and curing was performed to obtain a PMMA film with a surface coating, the coating thickness of which was 5 μm. The original film performance test is shown in Table 1.
[0125] A method for preparing a polarizer, comprising the following steps:
[0126] S1. Unwind the PVA original film at the first unwinding position, and perform swelling, dyeing, bridging, stretching, washing, fixing and drying to obtain PVA polarizers; adhere a PMMA film material with a surface coating and a PMMA film material without a surface coating to the upper and lower surfaces of the PVA polarizers respectively by UV glue, the PMMA film material with a surface coating is an outer layer, the PMMA film material without a surface coating is an inner layer, and a PSA glue layer is adhered to the inner layer.
[0127] S2, unwind the release film at the second unwinding station, apply PSA glue, dry it in a drying oven, adhere it to the inner layer, and rewind it.
[0128] S3, the upper semi-finished polarizer is unwound on the cutting line, and is cut and edge-grinded to obtain a finished polarizer sheet.
[0129] The performance test of the polarizer without surface protective film is shown in Table 1.
[0130] Comparative Example 3 (Epoxy resin ratio is not within the specified range, surfactant is lower than the specified value)
[0131] Preparation of coating composition:
[0132]
[0133] First add ε-caprolactone monomer and toluene into the preparation barrel and stir to mix evenly, then add CELLOXIDE2021P, CYCLOMER M100, OXT-221 (DOX), pentaerythritol tetraacrylate in turn and stir to mix evenly, finally add KY-1203, diphenyl-(4-phenylthio)phenylsulfonium hexafluorophosphate (CPI-100P), and IRGACURE 184 and stir to mix evenly.
[0134] When preparing and storing the above environment, please avoid direct sunlight, you can turn on the yellow light.
[0135] A method for preparing a PMMA film with a surface coating, the steps are as follows:
[0136] The prepared surface coating composition was applied to the non-priming surface of the PMMA film (model HX-40UF), and after drying, UV irradiation and curing was performed to obtain a PMMA film with a surface coating, the coating thickness of which was 5 μm. The original film performance test is shown in Table 1.
[0137] A method for preparing a polarizer, comprising the following steps:
[0138] S1. Unwinding the PVA original film at the first unwinding position, swelling, dyeing, bridging, stretching, washing, fixing and drying to obtain the PVA polarizer; attaching the PMMA film material with surface coating and the PMMA film material without surface coating to the upper and lower surfaces of the PVA polarizer respectively by UV glue, the PMMA film material with surface coating is the outer layer, and the PMMA film material without surface coating is the inner layer.
[0139] S2, unwind the release film at the second unwinding station, apply PSA glue, dry it in a drying oven, adhere it to the inner layer, and rewind it.
[0140] S3, the upper semi-finished polarizer is unwound on the cutting line, and is cut and edge-grinded to obtain a finished polarizer sheet.
[0141] The performance test of the polarizer without surface protective film is shown in Table 1.
[0142] Comparative Example 4
[0143] The outer layer is a commercially available PMMA film material DS22S (HX-40UF) with surface coating, which needs to be attached with a surface protection film when used. The original film performance test is shown in Table 1.
[0144] Original film hardness test: stick the test sample (5cm*15cm) with the coated surface facing up on the glass, use a pencil hardness meter at a load of 500g, use a Mitsubishi standard pencil, and make the pencil and sample contact at a 45° angle. Draw 5 lines of about 1cm on the test piece at 0.5-2mm / s. Remove the sample from the glass and erase the pencil marks on the surface with an eraser. Visually observe whether there are scratches on the test piece. If there are less than 3 scratches, it is judged that the pencil hardness of this level is qualified.
[0145] Original film wear resistance test: stick the test sample (5cm*15cm) with the coated surface facing up on the glass, fix it on the friction tester, use 500g load, use 0000# steel wool to draw a 5cm line on the coated surface at 50mm / s, count as one time, a total of 20 times, remove the sample from the glass, and visually observe whether there are scratches on the test piece. If there are scratches, it is judged as unqualified for the friction test of this level. If there are no scratches, it is judged as qualified.
[0146] Original film water vapor permeability test: Use a water vapor permeability cup to measure, put 30g±0.2g of desiccant into the water vapor permeability cup, fix the sample surface coating to the water vapor permeability cup with a black fixture, lock it tightly, put it into a constant temperature and humidity machine (temperature: 40℃; humidity: 90%RH) for 24 hours, weigh it immediately after taking it out, and record the data. Substitute it into the formula to calculate: Water vapor permeability unit g / m 2 ·24h.
[0147] Water vapor permeability calculation formula: (m t -m0 ) / π*r 2
[0148] m t : Weight after placing the constant temperature and humidity machine, m 0 : Weight before placing the constant temperature and humidity machine.
[0149] Table 1 Performance test table of polarizers prepared in embodiments and comparative examples
[0150]
[0151] It can be seen from the data in the table that the polarizer without a surface protective film in the present application has excellent anti-fouling and anti-fingerprint properties, high hardness, good wear resistance, and low moisture permeability. In Comparative Example 1, no methacrylate with alicyclic epoxy groups is added, and the surfactant is higher than the limit value. The moisture permeability of the original film with a surface coating is too large, which is easy to cause poor blisters of the polarizer and poor wear resistance. In Comparative Example 2, no hydrophobic acrylate is added, and the hardness of the original film with a surface coating is less than 3H, and the wear resistance is poor. In Comparative Example 3, the proportion of epoxy resin is not within the limit range, and the surfactant is lower than the limit value. The original film with a surface coating has poor wear resistance, and the moisture permeability is too large, which is easy to cause poor blisters of the polarizer, and there is also poor anti-fouling and anti-fingerprint performance. The outer layer of Comparative Example 4 is a commercially available PMMA film material DS22S (HX-40UF) with a surface coating, which has a low water contact angle, poor anti-fouling properties, poor surface coating hardness and wear resistance, and high moisture permeability, and requires a surface protective film to protect against scratches.
[0152] It should be emphasized that the above are only preferred embodiments of the present invention and do not limit the present invention in any form. Any simple modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention are still within the scope of the technical solution of the present invention.
Claims
1. A membrane material with a surface coating, characterized in that: The film material includes a base film and a surface coating coated on the non-priming surface of the base film. The coating liquid of the surface coating includes the following components in parts by weight: 10 to 30 parts of epoxy compound, 8 to 15 parts of hydrophobic acrylate, 0.5 to 2.0 parts of surfactant, 1.5 to 3.0 parts of photoinitiator, 3 to 8 parts of diluent and 50 to 65 parts of solvent.
2. The film material with surface coating according to claim 1, characterized in that: The epoxy compound includes a mixture of methacrylate and / or 1,2-epoxy-4-vinylcyclohexane of an alicyclic epoxy group containing a carbon-carbon double bond, an alicyclic epoxy compound without a carbon-carbon double bond, and oxetane, and the mixture ratio of the three is 2:2:
1.
3. The film material with surface coating according to claim 1, characterized in that: The hydrophobic acrylate includes an unsubstituted linear or branched alkyl acrylate having 1 to 5 carbon atoms or an unsubstituted aryl acrylate.
4. The film material with surface coating according to claim 3, characterized in that: The hydrophobic acrylate includes one or more of pentaerythritol tetraacrylate, dipentaerythritol hexaacrylate, ethylene glycol diacrylate, glycerol triacrylate and methyl acrylate.
5. The film material with surface coating according to claim 1, characterized in that: The surfactant includes a fluorine-containing acrylic compound, a fluorine-containing organosilicon compound or an organosilicon compound; the photoinitiator includes a mixture of a photocationic initiator and a photoradical initiator, and the weight ratio of the two is 1:1 to 3:
1.
6. The film material with surface coating according to claim 5, characterized in that: The photocationic initiator comprises diazonium salt, diaryliodonium salt, triarylsulfonium salt, alkylsulfonium salt, triarylsulfonium salt, iron arene salt, sulfonyloxy ketone, triarylsiloxane, diphenyl[4-(phenylthio)phenyl]-copper(II) hexafluoroantimonate, diphenyl-(4-phenylthio)phenylsulfonium hexafluorophosphate, 4-isobutylphenyl-4-( ... , - one or more of methylphenyliodonium hexafluorophosphate and isopropylthioxanthone; the photo-radical initiator includes one or more of phenyl ketone, phosphorus, triazine, acetophenone, benzophenone, thioxanthone, benzoin, and oxime compounds.
7. The film material with surface coating according to claim 1, characterized in that: The diluent includes ε-caprolactone monomer or epoxy resin monomer; the solvent includes one or more of toluene, butanone, ethyl acetate, butyl acetate, methyl isobutyl ketone, and propylene glycol methyl ether acetate.
8. The film material with surface coating according to claim 1, characterized in that: The thickness of the surface coating is 4-8 μm; the base film is a PMMA film or a PET film.
9. A polarizer, characterized in that: The film material with surface coating as described in any one of claims 1 to 8 is applied to the polarizer, and the polarizer comprises, from top to bottom, a film material with surface coating, a PVA polarizer, a film material without surface coating, a pressure-sensitive adhesive, and a release film, and the film material with surface coating and the film material without surface coating are respectively bonded to the upper and lower surfaces of the PVA polarizer by UV adhesive.
Citation Information
Patent Citations
hydrophilic, breathable, allergen-proof, allergen-free outer fabrics
DE20000027U1